Outcomes of a Clinical Pathway for Pleural Disease Management: “Pleural Pathway” - Srinivas R. Mummadi; Peter Y. Hahn (Pulmonary Medicine)
Background and Objectives. Clinical pathways are evidence based multidisciplinary team approaches to optimize patient care. Pleural diseases are common and accounted for 3.4 billion US $ in 2014 US inpatient aggregate charges (HCUPnet data). An institutional clinical pathway (“pleural pathway”) was implemented in conjunction with a dedicated pleural service. Design, implementation, and outcomes of the pleural pathway (from August 1, 2014, to July 31, 2015) in comparison to a previous era (from August 1, 2013, to July 31, 2014) are described. Methods. Tuality Healthcare is a 215-bed community healthcare system in Hillsboro, OR, USA. With the objective of standardizing pleural disease care, locally adapted British Thoracic Society guidelines and a centralized pleural service were implemented in the “pathway” era. System-wide consensus regarding institutional guidelines for care of pleural disease was achieved. Preimplementation activities included training, acquisition of ultrasound equipment, and system-wide education. An audit database was set up with the intent of prospective audits. An administrative database was used for harvesting outcomes data and comparing them with the “prior to pathway” era. Results. 54 unique consults were performed. A total of 55 ultrasound examinations and 60 pleural procedures were performed. All-cause inpatient pleural admissions were lower in the “pathway” era (n=9) compared to the “prior to pathway” era (n=17). Gains in average case charges (21,737$ versus 18,818.2$/case) and average length of stay (3.65 versus 2.78 days/case) were seen in the “pathway” era. Conclusion. A “pleural pathway” and a centralized pleural service are associated with reduction in case charges, inpatient admissions, and length of stay for pleural conditions.